Reactive infectious mucocutaneous eruptions associated with SARS-CoV-2 infection - John, Shaji Thomas; K., Gayathri; P., Rizwana; Martin, Abhay M. (International Journal of Contemporary Pediatrics, 2021)
Several dermatological manifestations are described in COVID-19. A 3-year-old boy presented with fever, painful oral ulcers with COVID-19 infection. A diagnosis of reactive infectious mucocutaneous eruptions (RIME) was made. He was worked up for the usual causes of RIME but were all negative. His severe acute respiratory syndrome corona virus-2 immunoglobulin M (SARS-CoV-2 IgM) was positive and he was managed with Intravenous hydrocortisone with which he improved dramatically. RIME might be the first/only manifestation of COVID-19 and it should be kept in mind.